How Long Is the Maturity of Corporate Borrowing? Evidence from Bond and Loan Issuances across Markets - Cortina-Lorente, Juan Jose (World Bank E-Library Archive, 2016)
This paper studies the extent to which access to domestic and international bond markets and syndicated loan markets and switches across them impact corporate debt maturity. Using world issuance activity during 1991-2014, the paper shows that different markets provide financing at different terms and that the importance of each market varies over time. Thus, the type of debt issued and its composition affect corporate maturity. During the global financial crisis of 2008-09, firms issued more bonds and, in developing countries, also more domestic loans. Because these markets are of longer maturity, the substitution across them allowed the largest firms that switched markets to maintain their average borrowing maturity, even when the maturity within each market declined for switchers and non-switchers. This evidence suggests that firms use different debt markets as complements and substitutes, and that compositional effects across firms and markets have a material impact on firm-specific and aggregate maturity